In‐And‐Outers and Moonlighters: An Evaluation of the Impact of Policy‐making Exposure on IR Scholarship1. Issue 1 (15th April 2013) - Parks, Bradley C.; Stern, Alena
<x xml:space="preserve">Abstract</x> Some international relations (IR) scholars lament the divide that exists between the academic community and the policy community. Others celebrate it. In this article, we test a core proposition advanced by advocates of bridging the policy‐academy divide: that direct engagement in the policy‐making process will make international relations scholars more adept at designing, undertaking, and communicating research in ways that are useful and relevant to policymakers. Using a difference‐in‐differences estimation strategy, we evaluate whether and to what extent direct exposure to the policy‐making process influences how IR scholars select publication outlets. We define and evaluate policy‐making exposure in two ways: periods of public service in which faculty members temporarily vacate their university positions to work for governments or intergovernmental organizations; and instances in which faculty members undertake substantial consulting assignments for government agencies and intergovernmental organizations. Our findings suggest that "in‐and‐outers"—faculty members who temporarily leave the ivory tower to accept policy positions—return to the academy with new perspectives and publication priorities. By contrast, we find no policy‐making exposure effect among "moonlighters." Our results suggest that IR scholars are no more likely to publish in policy journals after doing part‐time consulting work for governments and IOs.